TRADISI BUWUHAN PADA PELAKSANAAN WALIMATUL ‘URSI PERSPEKTIF URF (Studi Kasus di Dusun Wonosari Desa Sekarbagus Kec. Sugio Kab. Lamongan) - Ahmad Ikmaluddin Chafid; Masrokhin Masrokhin (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
The buwuhan tradition is a tradition of donating to sohibul walimah either material or non-material, with the aim of connecting the friendship between the giver and receiver. The buwuhan tradition has been running for quite a long time and for generations, the buwuhan tradition is also carried out in various regions of Java, one of which is in Wonosari Hamlet, Sekarbagus Village, Sugio District, Lamongan Regency.This study aims to: 1.) to find out how the practice of buwuh tradition in the implementation of walimatul 'ursi in Wonosari Hamlet 2.) and to know the 'urf perspective on the buwuh tradition in Wonosari Hamlet.In this study using qualitative methods, namely field research using phenological approaches and 'urf. Data obtained through observation, interviews, and documentation to the people of Wonosari Hamlet, data analysis using descriptive analysis.From the results of this study, the tradition of buwuh in Wonosari Hamlet is a hereditary tradition since the time of the ancestors, the tradition of buwuh in Wonosari Hamlet is a voluntary tradition of buwuh with the aim of sodaqoh without any conditions to be returned.The buwuhan tradition in Wonosari Hamlet is 'urf 'am which is a tradition that is commonly carried out in various regions, and is included in the category of 'urf shahih which is a good custom that does not contradict sharia and the Quran